Beyond visible: giant bulk photovoltaic effect for broadband neuromodulation - Xueping Chai; Zhipei Sun (Light: Science & Applications)
Abstract The giant bulk photovoltaic effect in tellurene nanomaterials has been harnessed to enable broadband infrared neuromodulation, expanding the potential for safe, non-invasive neural stimulation and highlighting the importance of material innovation in advancing infrared photonic applications.